Case Report: Hereditary Fibrosing Poikiloderma With Tendon Contractures, Myopathy, and Pulmonary Fibrosis (POIKTMP) Presenting With Liver Cirrhosis and Steroid-Responsive Interstitial Pneumonia - Takimoto-Sato, Michiko; Miyauchi, Toshinari; Suzuki, Masaru; Ujiie, Hideyuki; Nomura, Toshifumi; Ikari, Tomoo; Nakamura, Tomohiko; Takahashi, Kei; Matsumoto-Sasaki, Machiko; Kimura, Hirokazu; Kimura, Hiroki; Matsui, Yuichiro; et al. (Frontiers in Genetics, 2022)
Background: Hereditary fibrosing poikiloderma with tendon contractures, myopathy, and pulmonary fibrosis (POIKTMP) is an extremely rare disease caused by mutations in FAM111B, and only approximately 30 cases have been reported worldwide. Some patients develop interstitial pneumonia, which may lead to progressive pulmonary fibrosis and poor prognosis. However, no effective treatment for interstitial pneumonia associated with POIKTMP has been reported. Here, we report an autopsy case of POIKTMP, wherein interstitial pneumonia was improved by corticosteroids. Case Presentation: A 44-year-old Japanese man was referred to our hospital due to poikiloderma, hypotrichosis, and interstitial pneumonia. He developed progressive poikiloderma and muscle weakness since infancy. He also had tendon contractures, short stature, liver cirrhosis, and interstitial pneumonia. Mutation analysis of FAM111B revealed a novel and de novo heterozygous missense mutation, c.1886T > G (p(Phe629Cys)), through which we were able to diagnose the patient with POIKTMP. 3 years after the POIKTMP diagnosis, interstitial pneumonia had worsened. After 2 weeks of administrating 40 mg/day of prednisolone, his symptoms and lung shadows improved. However, he subsequently developed severe hepatic encephalopathy and eventually died of respiratory failure due to bacterial pneumonia and pulmonary edema. Autopsy revealed an unclassifiable pattern of interstitial pneumonia, as well as the presence of fibrosis and fatty degeneration in several organs, including the liver, kidney, skeletal muscle, heart, pancreas, and thyroid. Conclusions: We report a case of POIKTMP in which interstitial pneumonia was improved by corticosteroids, suggesting that corticosteroids could be an option for the treatment of interstitial pneumonia associated with this disease.